PENGARUH PENGGUNAAN BIJI PLASTIK SEBAGAI SUBSTITUSI AGREGAT HALUS TERHADAP MUTU BETON RINGAN - Arsyad, M. Rosihan; Mulyati, Ely (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This research aims to analyze the effect of using recycled plastic granules as a partial substitute for fine aggregate on the mechanical properties of lightweight concrete, with the background of reducing the exploitation of natural aggregate and addressing plastic waste issues. The experimental method involved creating cylindrical concrete test specimens with a design strength of Fc' 25 MPa, which included normal concrete and concrete with fine aggregate substitution by plastic granules at 5%, 7.5%, and 10%. Test results showed that the optimal substitution occurred at 7.5%, which produced the highest compressive strength of 25.01 MPa at 28 days, exceeding normal concrete (24.06 MPa), while also providing optimal values for split tensile strength (2.55 MPa) and modulus of elasticity (24,958.55 MPa). While the 5% substitution still showed improvement, the 10% substitution actually caused a decrease in performance. It was concluded that the use of plastic granules as a substitute for fine aggregate up to 7.5% has the potential to produce more environmentally friendly lightweight concrete with better mechanical performance, while substitution above that level is no longer optimal.Keywords: Lightweight Concrete, Plastic Granules, Fine Aggregate Substitution, Compressive Strength, Split Tensile Strength, Modulus of Elasticity